ChemInform Abstract: Recent Advances in the N‐Heterocyclic Carbene (NHC)‐Organocatalyzed Stetter Reaction and Related Chemistry. Issue 29 (July 2015) - Yetra, Santhivardhana Reddy; Patra, Atanu; Biju, Akkattu T.
Abstract Review: [94 refs.